Hollow and hemispherical bowl-like hollow carbon spheres and their doped counterparts as supports for platinum for use in fuel cell oxygen reduction reactions - Mashindi, Victor (My University, 2021)
Proton exchange membrane fuel cells (PEMFCs) are being used in the automobile industry as one of the replacements for gasoline powered engines. This is because PEMFCs have many advantages over traditional engines including their being light weight and that they are a cleaner energy conversion system. There are, however, challenges with PEMFCs. These include their low durability due to dissolution of the metal catalysts; the electrochemical oxidation of the carbon supports that are used due to the corrosive acid media found in PEMFCs, and the highly oxidising potentials reached during start up or during load cycling. Therefore, there is a quest to find highly active catalysts that are durable, and which are essential for the full-scale commercialization of PEMFCS for a range of applications such as in automobiles and home power generation systems. Even though other corrosion resistant supports like metal oxides and doped metal oxides have been used to replace carbon supports, their low conductivity and high cost still makes carbon- or carbon-based supports more attractive. Many carbon supports have only shown low durability, but new and novel structured carbon supports have been shown to have a wide range of favourable properties that can make them suitable and durable ORR catalyst supports. Metal-free nitrogen doped structured carbons have also shown catalytic activity and durability towards ORR. In this study new hollow carbon spheres and hemispherical broken bowl-like carbons have been used as carbon supports for potential use in PEMFCS. Hollow, graphitic, mesoporous carbon spheres (HCSs) and their nitrogen doped counterparts (NHCSs) have been made to use as supports for the synthesis of highly active and durable Pt oxygen reduction reaction (ORR) catalysts. HCSs with a large diameter (~ 318 nm) were made by a templating method using Stober spheres as the template. A post synthesis technique using melamine was used to dope the surface of the HCSs with nitrogen to give NHCSs (d ~ 320 nm). Smaller aggregated silica templates were also made and iii were used as templates to form hemispherical, broken bowl like hollow carbon spheres (BHCSs) with a diameter of ~ 58 nm. A post synthesis technique (also using melamine) was used to make nitrogen doped broken bowl like hollow carbon spheres (BNHCSs) with a diameter of ~ 60 nm. A metal-organic deposition technique was used to deposit Pt nanoparticles on the different carbon supports and these materials were used to study the Pt catalyst on the different supports for ORR activity and durability. Also, for comparison, a reflux method was used to deposit Pt particles on the HCS and NHCS and the materials were also studied for ORR activity and durability. The spherical and hemispherical morphology of the supports was confirmed by TEM and SEM analysis. Raman spectra confirmed the incorporation of defects due to nitrogen doping while the thermal stability of the pristine supports was significantly lowed upon nitrogen doping. Nitrogen incorporation on the doped supports, XPS (4.2 - 5.5 atomic %) was found to be due to the presence of pyridinic, graphitic, pyrrolic nitrogen, metal-N-pyridyl groups as well as the oxidised nitrogen groups. Surface oxidation of the supports was significantly decreased upon nitrogen doping. TGA confirmed a loading of about 40 wt.% Pt on the supports and that the thermal stability of the supports decreased upon metal nanoparticle decoration. The supports were decorated with Pt nanoparticles (d = 3.8 – 4.6 nm) with Pt – Pt distances between 5.8 – 6.5 nm on all supports. ADF-BF-STEM and in-situ PXRD studies confirmed pore confinement of the Pt which enhanced the durability of the catalysts. Nitrogen doped supports had smaller Pt particle sizes (d = 4.0 ± 0.6 nm (Pt/HCSs) and d = 4.6 ± 0.9 (Pt/BNHCSs)) and shorter Pt - Pt distances between 5.8 – 6.5 nm. ORR studies were performed on the Pt/BHCSs, Pt/BNHCSs, Pt/HCSs and the Pt/NHCSs catalysts. The materials exhibited ECSA values between 50 – 69 m2 .g-1 consistent with the Pt particle sizes obtained from TEM. The obtained mass activity (MA) was between 90 – 263 A.g-1 compared to between 65 - 203 A.g-1 for the commercial Pt/Vulcan benchmark catalyst. iv The obtained surface area specific activity was between 134 – 391 µA.cm-2 compared to 107 – 350 µA.cm-2 for the commercial benchmark catalyst. After 6000 durability cycles, the catalysts retained between 57.2 – 65.4 % of the initial ECSA compared to 47.6% for the commercial benchmark catalyst. Enhanced activity in ORR of the catalysts was attributed to the small Pt particle sizes, the thin carbon shells that enabled better electronic conductivity and faster mass transport of reactive gases. The presence of nitrogen in the support also modified the electronic structure of the Pt. For the smaller Pt/BHCSs and Pt/BNHCSs catalysts, the very thin support shell (d = 4.5 – 4.6 nm) promoted higher Pt utilization of the supports. A better electronic conductivity resulted in better activity. Our studies thus confirmed that the high activity and durability of the catalysts could be attributed to a thin graphitic mesoporous shell, the presence of defects and the presence of nitrogen functionalities. Nitrogen doping altered the electronic state of the Pt. The thinner and broken shells of the Pt/BHCSs and Pt/BNHCSs materials allows for deposition of Pt on either side of the support thereby enhancing the electronic conductivity and gas mass transport of the materials leading to higher activity. We also confirmed that different synthetic procedures for Pt nanoparticles can yield Pt particles with comparable ORR activity.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2021